High-Dose Dexamethasone Alters the Increase in Interleukin-16 Level in Adult Immune Thrombocytopenia - Wang, Xinru; Li, Lizhen; Wang, Yuanjian; Li, Xin; Feng, Qi; Hou, Yu; Ma, Chunhong; Gao, Chengjiang; Hou, Ming; Peng, Jun (Frontiers in Immunology, 2019)
Adult primary immune thrombocytopenia (ITP) is an autoimmune-mediated haemorrhagic disorder. Interleukin-16 (IL-16) can directly effect on cellular or humoural immunity by mediating the cellular cross-talk among T cells, B cells and dendritic cells. Several studies have focused on IL-16 as an immunomodulatory cytokine that takes part in Th1 polarization in autoimmune diseases. In this study, we investigated the differences in IL-16 expression in the bone marrow and blood of ITP patients and healthy controls. Furthermore, we detected the changes in blood IL-16 expression before and after the single-agent 4-day high-dose dexamethasone (HD-DXM) therapy. In patients with active ITP, bone marrow supernatant and plasma IL-16 levels increased (P < 0.05) compared with those of healthy controls. In the meantime, the gene expression in BMMCs (pro-IL-16, caspase-3) and PBMCs of ITP patients (pro-IL-16, caspase-3 and T-bet) was increased (P < 0.05) relative to those of healthy controls. In patients who responded to HD-DXM therapy, both plasma IL-16 levels and gene expression in PBMCs (pro-IL-16, caspase-3 and T-bet) were decreased (P < 0.05). In summary, the abnormal level of IL-16 plays important roles in the pathogenesis of ITP. Importantly, regulating Th1 polarization associated with IL-16 by HD-DXM therapy may represent a novel insight for immune modulation in ITP.